Pengembangan Motif Batik Sasambo dengan Sistem Lindenmayer - Subaiah Marlina; Qurratul Aini; I Wayan Sudiarta (University of Mataram, 2020)
Batik is an Indonesian intangible cultural heritage that needs to be preserved. Indonesia has a variety of batik patterns such as Sasambo (Sasak, Samawa, and Mbojo) batik patterns from West Nusa Tenggara. This study aims to develop Sasambo batik patterns by using the Lindenmayer System (L-System). The Sasambo batik patterns developed in this study are of two types: Lumbung (rice barn) and Kangkung (water spinach) patterns. By applying the L-System, there are three different ways that can be done, namely (1) making the Sasambo batik patterns as axioms, (2) making the batik patterns as generators, and (3) combining the Sasambo patterns with fractals. Based on the new patterns produced using the L-System, the selection of generators should have the initial and final segments which are both in a single line position, so that the original patterns unchanged.